Preoperative management of children with esophageal atresia: current perspectives - Parolini F; Bulotta AL; Battaglia S; Alberti D (Dove Medical Press, 2017)
Filippo Parolini,1 Anna Lavinia Bulotta,1 Sonia Battaglia,1 Daniele Alberti1,2 1Department of Pediatric Surgery, “Spedali Civili” Children’s Hospital, 2Department of Clinical and Experimental Sciences, University of Brescia, Brescia, Italy Abstract: Esophageal atresia remains one of the most challenging congenital anomalies of the newborn. In recent years, because of the advances in prenatal diagnosis, neonatal critical care, and surgical procedures, overall outcomes have improved substantially, including for premature children. Nowadays, most of the research is focused on medium- and long-term morbidity, with particular reference to respiratory and gastroesophageal problems; the high frequency of late sequelae in esophageal atresia warrants regular and multidisciplinary checkups throughout adulthood. Surprisingly, there are few studies on the impact of prenatal diagnosis and there is continuing debate over the prenatal and preoperative management of these complex patients. In this review, we analyze the literature surrounding current knowledge on the management of newborns affected by esophageal atresia, focusing on prenatal management and preoperative assessment. Keywords: prenatal diagnosis, esophageal atresia, tracheoesophageal fistula, ultrasound scan, tracheobronchoscopy